Trends of Enterovirus D68 Concentrations in Wastewater, California, USA, February 2021–April 2023 - Alexandria B. Boehm; Debra A. Wadford; Bridgette Hughes; Dorothea Duong; Alice Chen; Tasha Padilla; Chelsea Wright; Lisa Moua; Teal Bullick; Maria Salas; Christina Morales; Bradley J. White; et al. (Emerging Infectious Diseases, 2023)
In this retrospective study, we measured enterovirus D68 (EV-D68) genomic RNA in wastewater solids longitudinally at 2 California, USA, wastewater treatment plants twice per week for 26 months. EV-D68 RNA was undetectable except when concentrations increased from mid-July to mid-December 2022, which coincided with a peak in confirmed EV-D68 cases.